A "seasonal bromoderma" in a farmer. Issue 1 (21st October 2018) - Pranteda, Guglielmo; Magri, Francesca; Muscianese, Marta; D'Arino, Andrea; Pranteda, Giulia; Fidanza, Laura; Bartolazzi, Armando
Abstract: Bromoderma is a rare skin disease caused by the ingestion, inhalation, or contact with products containing bromides. We report a case of bromoderma in a 36‐year‐old farmer, characterized by remission during the spring and exacerbation during the winter. The recognition of the use of products containing bromides during the winter helped us to understand the cause of the clinical condition.